T-cell signaling in allogeneic bone marrow transplantation - Sydney X. Lu; Melanie Chow; Vanessa M. Hubbard; David Suh; T.D. Kim; Adam A. Kochman; J.L. Zakrzewski; Javier Cabrera-Pérez; Önder Alpdoğan; Marcel R.M. van den Brink (2006)
We examined the signaling profiles of T cells in murine allogeneic bone marrow transplantation with a novel high-throughput technique to analyze activation of signaling pathways by flow cytometry. We first studied normal splenic, liver, and peripheral lymph node (PLN) T cells. Relative to naive CD4 and CD8 cells, effector and memory cells displayed nearly global increases in activation of signaling pathways including MEK1/2 and PKC (both up ∼10-fold), and S6 ribosomal protein (∼6 fold) (Table 1). In the thymus, there was a general lack of signaling activity in CD4+CD8+ cells, and these did not respond to cytokines. By contrast, CD4−CD8− (DN) cells of the DN1 and DN2 stage had the greatest signaling activity of all subsets. CD4+, CD8+, and DN cells responded to the cytokines IL-7 and IL-15 by phosphorylating STAT-5A (∼10 fold). We then studied alloreactive and homeostatically proliferating T cells by infusion of CFSE labeled cells into irradiated hosts. We noted a gradual and global increase in signaling activity with each cell division in the spleen, liver, and PLN. Molecules that were phosphorylated included c-Raf, MEK1/2, ERK1/2, Akt, STAT-1, STAT-3, STAT-4, and S6 ribosomal protein. Tacrolimus and cyclosporin inhibited both cell cycling and increases in signaling. We defined slow-cycling cells as homeostatically expanding and fast-cycling cells as alloreactive, and found a distinct signaling pattern in homeostatically expanding T cells, with lower levels of MAP kinase pathway activity and STAT pathway activity. We hypothesize that this difference can be attributed to strong IL-2 and TCR signaling in alloreactive cells through the MAP kinases, Akt and STAT-3, by IFNγ for STAT-1, and by IL-12 for STAT-4. In the setting of T-cell depleted bone marrow transplantation, we found in several models that bone marrow-derived splenic T cells had signaling levels generally comparable with that of the naive populations in a normal spleen, but with a deficiency in STAT-3 phosphorylation. In the thymus, we observed a defect in Akt signaling in all subsets relative to signaling levels in the normal thymus, with up to 100-fold decreases. The defect persisted up to day 28 post-transplant. We conclude that the high-throughput analysis of signaling activity in T cells during allogeneic BMT allows for the definition of distinct signaling profiles. These signaling signatures can be used for the development of targeted therapies to enhance or inhibit specific T cell subsets.Table 1Signaling in the C57BL/6 SpleenCD4CD8Naive(CD44lo CD62Lhi)Effector(CD44hi CD62Llo)Memory(CD44hi CD62Lhi)Naive(CD44lo)Effector/Memory (CD44hi)c-Raf (pS259)12.21.811.2MEK 1/2 (pS217/pS221)12.79.712.2ERK 1/2 (pT202/pY204)11.61.811.2JNK (pT180/pY182)11.16.512.3pan-p38 (pT180/pY182)12.13.011.8pan-Akt (pT308)12.13.811.4pan-Akt (pS473)12.63.911.7Pan-PKC (βII pS660)12.710.111.4STAT-1 (pY701)10.96.312.4STAT-3 (pY705)11.41.811.3STAT-3 (pS727)11.21.311.3STAT-4 (pY693)12.02.311.2STAT-5A (pY694)11.31.711.3S6 ribosomal protein (pS235/pS236)13.06.311.8Histone H2B (pS14)12.64.211.8PIP211.30.410.6Ratio of activation (phosphorylation) of signaling molecules in effector or memory CD4 or CD8 cells compared with corresponding naive CD4 or CD8 cells. Open table in a new tab Ratio of activation (phosphorylation) of signaling molecules in effector or memory CD4 or CD8 cells compared with corresponding naive CD4 or CD8 cells.